Correlation between emotional intelligence and negative emotions of front‐line nurses during the COVID‐19 epidemic: A cross‐sectional study. Issue 3 (21st January 2021) - Sun, Huili; Wang, Shuling; Wang, Wei; Han, Guanghong; Liu, Zhijian; Wu, Qi; Pang, Xiaoli
Abstract: Aims and Objectives: The purpose of this study was to understand the emotional intelligence level (EI) and negative emotional status of the front‐line nurses in the epidemic situation and to further explore the relationship between them. Background: During the COVID‐19 epidemic, under the influence of multiple factors, nurses were vulnerable to negative emotions. While previous studies have explored, the role of emotional intelligence in negative emotions, the relationship between the two has not been sufficiently discussed in the context of COVID‐19. Design: The study carried out a cross‐sectional survey. The STROBE was selected as the checklist in this study. Methods: 202 nurses from Wuhan makeshift hospital participated in the questionnaire survey. Data collection tools included a general data questionnaire designed by the researchers, Chinese version of EI scale (WLEIS‐C) and Chinese version of Depression Anxiety Stress Scale (DASS‐21). Descriptive statistics, single factor analysis and correlation analysis were used to analyse the data. Results: The emotional intelligence of the front‐line nurses was in the upper middle range. Among the negative emotions, anxiety was the most prominent symptom. Conclusions: Managers should pay attention to the negative emotional problems of front‐line nurses, improve their EI level and promote mental health and the progress of epidemic prevention. Relevance to clinical practice: Improving the level of emotional intelligence can reduce the frequency and intensity of negative emotions. In clinical work, emotional intelligence can be used as a skill to carry out relevant training, which is conducive to playing a positive role in future emergencies.